1986
DOI: 10.1021/la00069a002
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence properties of dansyl groups covalently bonded to the surface of oxidatively functionalized low-density polyethylene film

Abstract: The point of zero charge (PZC), the surface acidity constants pK1 and pK2, and the concentration of the charged surface groups A10H2+ and AlO" throughout the pH range 3.0-11.0 were determined by potentiometric acid-base titrations for a series of 7-aluminas used in industry as carriers which contain various amounts of sodium and silicon. Moreover, these surface parameters were determined for a modified carrier prepared by deposition of sodium on the 7-Al203 surface. It was found that the PZC, pKu pK2, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 6 publications
2
46
0
Order By: Relevance
“…In the sessile drop method, the penetration depth assumed to be < 1 nm and in the Wilhelmy plate wetting method, the absorption of liquids is assumed to be > 1 nm. This assumption of penetration depth is supported by a series of reports by Holmes-Farley and Whitesides (1986 and . According to the presented results, it is evident that the penetration enhances the basic and reduces the acid properties of wood.…”
Section: Surface Energy and Acid-base Properties Of Woodmentioning
confidence: 58%
“…In the sessile drop method, the penetration depth assumed to be < 1 nm and in the Wilhelmy plate wetting method, the absorption of liquids is assumed to be > 1 nm. This assumption of penetration depth is supported by a series of reports by Holmes-Farley and Whitesides (1986 and . According to the presented results, it is evident that the penetration enhances the basic and reduces the acid properties of wood.…”
Section: Surface Energy and Acid-base Properties Of Woodmentioning
confidence: 58%
“…First, the titratable groups seem to comprise a single population: they fit a single titration curve with a single value of pK1/2 [23]. Second, a significant, non-zero PAC signal is observed for values of pH where no signal is expected, based on our previous observations [5]. The origin of this background is not presently understood.…”
Section: Measurement Of Surface Aciditymentioning
confidence: 85%
“…1). For specificity, we will illustrate points using 'polyethylene carboxylic acid' (PE-Co2H), a material about which we have accumulated a substantial body of background information [2][3][4][5][6][7][8][9][10]. PE-CO,H is prepared by oxidation of lowdensity polyethylene film with chromic acid solution under specified conditions.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic absorbance of hydroxyl group was not detected with attenuated total reflectance infrared spectroscopy (ATR-IR) [21], however Blais et al reported hydroxyl groups introduced with chromic acid etching [21]. It was also found in a different study that chromic acid treatment increased carbonyl concentration from 0.4% of surface carbons to 11% of carbon [23].…”
Section: Influence Of Carbonyl Groups On Electrical Properties Of Polmentioning
confidence: 99%